GREEN ECONOMY AS A TOOL FOR SUSTAINABLE ECONOMIC GROWTH - Бабаева Сабинабону Давронбек қизи (Web of Journals Publishing, 2025)
The article explores the role of the green economy as a key instrument for achieving sustainable economic growth without compromising the natural environment. It analyzes the theoretical foundations of the concept, global challenges, and international practices. A comparative table is presented with examples of countries implementing green strategies, demonstrating the possibility of aligning economic and environmental interests.
Keywords: Green economy, sustainable development, CO₂ emissions, environmental policy, economic growth.